2007
DOI: 10.1080/09687590701725757
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service users’ experiences of returning to paid employment

Abstract: 196 3457 3 Mental health service users' experiences of returning to paid employmentResearch into mental health and employment has focused largely on people who are unemployed. This paper reports the experiences of 20 clients of employment support agencies who had succeeded in returning to work. A number of barriers to getting back to work were identified, but receiving employment support could enable people to overcome them. There was consistency with previous studies of factors associated with high and low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 6 publications
3
71
0
1
Order By: Relevance
“…When service users have been asked about their primary motivation for employment, the internalized values of being a worker, the satisfaction of belonging to a normal, encouraging but challenging working environment, and the possibilities of revitalization and empowerment are described (Auerbach and Richardson 2005;Borg and Kristiansen 2008;Gewurtz and Kirsh 2007;Iannelli and Wilding 2007;Kennedy-Jones, Cooper, and Fossey 2005;Kirsh 2000a;Krupa 2004). The literature also echoes dilemmas of revealing one's mental health history, when it comes to timing, processes and consequences (Boyce et al 2008;Honey 2004).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…When service users have been asked about their primary motivation for employment, the internalized values of being a worker, the satisfaction of belonging to a normal, encouraging but challenging working environment, and the possibilities of revitalization and empowerment are described (Auerbach and Richardson 2005;Borg and Kristiansen 2008;Gewurtz and Kirsh 2007;Iannelli and Wilding 2007;Kennedy-Jones, Cooper, and Fossey 2005;Kirsh 2000a;Krupa 2004). The literature also echoes dilemmas of revealing one's mental health history, when it comes to timing, processes and consequences (Boyce et al 2008;Honey 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Quite a few qualitative studies (Gewurtz and Kirsh 2007;Kennedy-Jones, Cooper, and Fossey 2005;Inman, McGurk, and Chadwick 2007;Iannelli and Wilding 2007;Rebeiro-Gruhl and Laporte 2008;Marwaha and Johnson 2005;Tse and Yeats 2002;Boyce et al 2008;Johnson et al 2009) have explored service users' past and present work experience within diverse vocational rehabilitation programs and employment settings. Gewutz and Kirsh (2007) revealed that through paid and unpaid work, individuals discovered their potential and became citizens with prospects of work.…”
Section: Vocational Rehabilitation Programsmentioning
confidence: 98%
See 1 more Smart Citation
“…The SESAMI (Social Inclusion through Employment Support for Adults with Mental Illness) study was a naturalistic investigation of the provision of supported employment for people with severe mental health problems in England in 2004-2006(Boyce et al, 2008aJohnson et al, 2009;SESAMI, 2007). Six agencies, among them public sector providers, private notfor-profit and voluntary organizations, participated.…”
Section: Introductionmentioning
confidence: 99%
“…potential; self-management strategies for staying well and coping with workplace stress; guidance during the job search; assistance to enable informed choices regarding disclosure; ongoing support from significant others; and feeling connected to others, welcomed, and respected at work (Boyce et al, 2008;Fossey & Harvey, 2010;Johnson et al, 2009;Woodside, Schell, & Allison-Hedges, 2006).…”
mentioning
confidence: 99%